Transcriptomic analysis of effects of 1-methylcyclopropene (1-MCP) and ethylene treatment on kiwifruit (Actinidia chinensis) ripening - Choi, Dasom; Choi, Jeong Hee; Park, Kee-Jai; Kim, Changhyun; Lim, Jeong-Ho; Kim, Dong-Hwan (Frontiers in Plant Science, 2023)
Ethylene (ET) is a gaseous phytohormone with a crucial role in the ripening of many fruits, including kiwifruit (Actinidia spp.). Meanwhile, treatment with 1-methylcyclopropene (1-MCP), an artificial ET inhibitor delays the ripening of kiwifruit. The objective of this study was to determine the effect of ET and 1-MCP application during time-course storage of kiwifruit. In addition, we aimed to elucidate the molecular details underlying ET-mediated ripening process in kiwifruit. For this purpose, we conducted a time-course transcriptomic analysis to determine target genes of the ET-mediated maturation process in kiwifruit during storage. Thousands of genes were identified to be dynamically changed during storage and clustered into 20 groups based on the similarity of their expression patterns. Gene ontology analysis using the list of differentially expressed genes (DEGs) in 1-MCP-treated kiwifruit revealed that the identified DEGs were significantly enriched in the processes of photosynthesis metabolism and cell wall composition throughout the ripening process. Meanwhile, ET treatment rapidly triggered secondary metabolisms related to the ripening process, phenylpropanoid (e.g. lignin) metabolism, and the biosynthesis of amino acids (e.g. Phe, Cys) in kiwifruit. It was demonstrated that ET biosynthesis and signaling genes were oppositely affected by ET and 1-MCP treatment during ripening. Furthermore, we identified a ET transcription factor, AcEIL (Acc32482) which is oppositely responsive by ET and 1-MCP treatment during early ripening, potentially one of key signaling factor of ET- or 1-MCP-mediated physiological changes. Therefore, this transcriptomic study unveiled the molecular targets of ET and its antagonist, 1-MCP, in kiwifruit during ripening. Our results provide a useful foundation for understanding the molecular details underlying the ripening process in kiwifruit.